Towards Fraternity: Mercy against Violence: Theological Reflections from Peruvian Prisons - Lecaros, Véronique (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
Based on a study of lived religion in two Peruvian prisons, this article explores the way in which a worldview rooted in images of an authoritarian God, conceived of as a supreme judge, and fosters a spiral of violence. Subhuman conditions are thus justified in prisons considered as human dumps. The exegetical and theological current that rehabilitates the Christian perspective of mercy in which the reflections of Pope Francis are framed, in particular, his last Encyclical Letter, Fratelli tutti, gives guidelines to establish another logic that allows restoring in their human dignity, individuals considered as disposable. Beyond a limited pastoral proposal, this article is about fostering relationships in society as a whole inspired by the Good Samaritan model.
Keywords: images of God; mercy and justice; prison ministry; religious conversion; Encyclical Letter Fratelli tutti